Pembelajaran Kooperatif Model Snowball Throwing Mampu Meningkatkan Prestasi Belajar Siswa pada Muatan PPKn di SDN 3 Srabah, Bendungan , Trenggalek - Sri Budiningsih (Universitas Muhammadiyah Ponorogo, 2021)
Learning achievement is greatly influenced by the learning experience. The learning experience is of course through various models and learning approaches, one of which is cooperative. One of the learning achievements that will be observed and studied is the content of citizenship education (PPKn). It is very important to instill civic education in students from an early age. This aims to instill the character of students who are in accordance with the foundations of the Republic of Indonesia which are contained in the 5 principles of Pancasila, for example being devotion, grateful, love for the country, unity and so on. Therefore, in order to improve students' learning achievement in PPKn content at SDN 3 Srabah, Bendungan District, Trenggalek Regency, a classroom action research was held using cooperative learning, the Snowball Throwing model by taking the subjects of this study were class III Semester I class students 2018 academic year. / 2019, amounting to 4 students. This research uses action research which is conducted in a cycle.This research was conducted in two cycles, where each cycle consisted of two meetings with a time allocation of 4 x lesson hours. Each cycle consists of four stages, namely planning, implementing, observing and reflecting. From the analysis of the research data, it was found that the students' average score was 65,00 in the first cycle increased to 82,50 in the second cycle. Student learning completeness also increased, where learning completeness in the first cycle was only 50%, in the second cycle it increased to 100%. So it can be concluded that learning the Snowball Throwing model can improve PPKn learning outcomes in class III Semester 1 students of the 2018/2019 academic year at SD Negeri 3 Srabah, Bendungan District, Trenggalek Regency.